Validitas Desain LKS Berorientasi Metode Ilmiah untuk Pencapaian Kompetensi Siswa dalam Pembelajaran Fisika pada Materi Gerak Melingkar dan Hukum Newton di Kelas X SMA/MA - Yosi Febriani; Amali Putra; Yenni Darvina (Universitas Negeri Padang, 2018)
The achievement’s competence of physic’s from the student is still slow. Some of the causes are limited implementation of the scientific approach in learning. Limited ability to think from student’s in answering questions that are creative, and limited learning resource that apply aspects of the scientific method. This study aims to produce LKS oriented scientific method’s are valid and practical to improve the achievement’s of student competence in physic lesson’s. The knowledge obtained by student’s in the form of scientific knowledge as obtained throught the steps of scientific methods.The type of research used is Research and Development (R&D) with the development model of ADDIE (Analysis, Design, Develop, Implementation and Evaluation) which is reduce into the develop stage. The reasearch subjects consisted of three lectures of FMIPA UNP as a validator. Three teachers of physic and one student class X MIA 5 SMA 16 Padang as a practitioner.The LKS validation test result that is 81,05% are on very valid criteria. The result of practice test result of LKS by teacher that is 88,33% are on very practical criteria, while the result practice test by student that is 84,07% are on very practical criteria. The result of this study indicate that LKS oriented scientific method worthy of use in physic learning for SMA/MA in term’s of validity and practicality.